Sustainable local tourism on digital government-based and community-based in Ciamis, Indonesia - Irfan Nursetiawan; Kiki Endah (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This study discusses the strategy of sustainable local tourism that integrates the digital government and community based tourism (CBT) approaches in Ciamis Regency. The diffusion of local culture and digitalization of the public sector are the main foundations in the formation and management of community-based pioneering tourism objects. Using a qualitative approach, this study reveals patterns of social interaction, the role of local actors, and the dynamics of collaboration between stakeholders in tourism development. The results of the study indicate that the practices of digital government through a tourism information system, integrated digital services, and participatory platforms can strengthen more inclusive, transparent, and adaptive tourism governance. Collaboration between local communities, local governments, academics, and industry players is an important prerequisite in realizing a sustainable smart tourism strategy. the digital integrated community based tourism (DICBT) model is offered as an innovation that can increase the competitiveness of destinations while strengthening the welfare of local communities in the digital era.